2022
DOI: 10.3390/ijerph19159139
|View full text |Cite
|
Sign up to set email alerts
|

Single Leg Cycling Offsets Reduced Muscle Oxygenation in Hypoxic Environments

Abstract: The intensity of large muscle mass exercise declines at altitude due to reduced oxygen delivery to active muscles. The purpose of this investigation was to determine if the greater limb blood flow during single-leg cycling prevents the reduction in tissue oxygenation observed during traditional double-leg cycling in hypoxic conditions. Ten healthy individuals performed bouts of double and single-leg cycling (4, four-minute stages at 50–80% of their peak oxygen consumption) in hypoxic (15% inspired O2) and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…To our knowledge, this is the first study to show that femoral blood flow was greater in response to maximal SL compared with DL cycling in both older and younger trained populations. Yet, these results are in agreement with observations of greater femoral blood flow during SL cycling in a limited cohort of healthy (n = 4) and clinical (patients with heart failure, n = 5) individuals (LeJemtel et al, 1986) and after submaximal SL cycling exercise (Burns et al, 2014;Draper et al, 2022). As such, this study supports the finding that a transition from large to small muscle mass exercise may allow for a greater peripheral hyperaemic response (Calbet et al, 2009;Cardinale et al, 2019;Klausen et al, 1982).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, this is the first study to show that femoral blood flow was greater in response to maximal SL compared with DL cycling in both older and younger trained populations. Yet, these results are in agreement with observations of greater femoral blood flow during SL cycling in a limited cohort of healthy (n = 4) and clinical (patients with heart failure, n = 5) individuals (LeJemtel et al, 1986) and after submaximal SL cycling exercise (Burns et al, 2014;Draper et al, 2022). As such, this study supports the finding that a transition from large to small muscle mass exercise may allow for a greater peripheral hyperaemic response (Calbet et al, 2009;Cardinale et al, 2019;Klausen et al, 1982).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, it has been shown that power output per leg is generally 5 to 10% greater during single-leg (SL) compared with double-leg (DL) cycling (Abbiss et al, 2011;Gordon et al, 2018;Iannetta et al, 2019). Yet, blood flow during maximal SL and DL cycling has only been assessed in a small clinical population (LeJemtel et al, 1986) or during submaximal exercise (Burns et al, 2014;Draper et al, 2022). Therefore, the improved capacity to increase blood flow and enhance oxygen delivery during a maximal cycling exercise performed using SL compared to DL remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%